2017
DOI: 10.1093/ckj/sfx124
|View full text |Cite
|
Sign up to set email alerts
|

Is progression of coronary artery calcification influenced by modality of renal replacement therapy? A systematic review

Abstract: BackgroundProgression of coronary artery calcification is an important marker for cardiovascular morbidity in end-stage renal disease patients. Therefore, we reviewed the evidence on coronary artery calcification progression in different renal replacement therapies.MethodsMEDLINE (PubMed), Embase and TRIP databases were searched from 1999 – 2016. Additionally, bibliographies were searched by hand and citation tracking of key publications was performed. Prospective studies were included that examined coronary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…We reported an abdominal artery calcification prevalence of 57.2% in our PD patients, in correspondence with published meta results in Asia population [4]. There were a few cross-sectional studies suggesting that abdominal artery calcification might be less common in PD patients compared to HD patients [14], while other studies reported no advantage of one modality over the other [4,17].…”
Section: Discussionsupporting
confidence: 88%
“…We reported an abdominal artery calcification prevalence of 57.2% in our PD patients, in correspondence with published meta results in Asia population [4]. There were a few cross-sectional studies suggesting that abdominal artery calcification might be less common in PD patients compared to HD patients [14], while other studies reported no advantage of one modality over the other [4,17].…”
Section: Discussionsupporting
confidence: 88%
“…We reported an abdominal artery calcification prevalence of 57.2% in our PD patients, in correspondence with published meta results in Asia population [4]. There were a few cross-sectional studies suggesting that abdominal artery calcification might be less common in PD patients compared to HD patients [14], while other studies reported no advantage of one modality over the other [4,17]. Vascular calcification is a sophisticated process and our results suggest both demographics and comorbidity might contribute to its development.…”
Section: Discussionsupporting
confidence: 88%
“…However, all of these studies had imbalances in age, dialysis vintage, or comorbidities between groups, which were not adjusted for statistically. In addition, the longitudinal study analyzed CAC progression as percentage change, which yields biased results because of the skewed distribution of CAC scores with excessive zeros [5]. The problematic distribution of CAC scores precludes many strategies commonly used to analyze changes.…”
Section: Discussionmentioning
confidence: 99%
“…This high cardiovascular mortality is strongly associated with vascular calcification [3,4], which occurs frequently [2] and progresses almost universally in end-stage renal disease [5]. Vascular calcification can be measured at various sites, such as the coronary arteries, and is promoted by phosphate, which is frequently elevated in end-stage renal disease [6,7].…”
Section: Introductionmentioning
confidence: 99%